Investigating translaminar signaling from layer 5 Pyramidal subpopulations to layer 2/3 in Somatosensory Cortex - Von Klemperer, A (2021)
Information processing in the mammalian cortex is achieved via a precise arrangement of synaptic connections between different neuronal subtypes. The excitatory neurons of the cortex are arranged in a laminar manner across six layers and form specific intralaminar and translaminar connections with one another. In addition, these excitatory neurons interact with a series of inhibitory interneuron subtypes, such that the relative levels and timing of excitatory and inhibitory synaptic transmission determine how information is processed by the cortical network. This thesis examines the translaminar signaling from layer 5 (L5) to layer 2/3 (L2/3) of cortex. Considered the principal output layer, L5 is populated by intratelencephalic (IT) and pyramidal tract (PT) pyramidal neurons, which form long-range projections to other cortical and subcortical regions, respectively. These long-range axons of L5 pyramidal neurons also branch locally and form ascending collaterals that extend to more superficial layers, including L2/3. An unanswered question in the field, is what sorts of translaminar signals do these local collaterals deliver.